Enzyme Architecture: The Role of a Flexible Loop in Activation of Glycerol-3-phosphate Dehydrogenase for Catalysis of Hydride Transfer - He, Rui (Biochemistry, 2018)
[Image: see text] The side chain of Q295 of glycerol-3-phosphate dehydrogenase from human liver (hlGPDH) lies in a flexible loop, that folds over the phosphodianion of substrate dihydroxyacetone phosphate (DHAP). Q295 interacts with the side-chain cation from R269, which is ion-paired to the substrate phosphodianion. Kinetic parameters k(cat)/K(m) (M(–1) s(–1)) and k(cat)/K(GA)K(HPi) (M(–2) s(–1)) were determined, respectively, for catalysis of the reduction of DHAP and for dianion activation of catalysis of reduction of glycolaldehyde (GA) catalyzed by wild-type, Q295G, Q295S, Q295A, and Q295N mutants of hlGPDH. These mutations result in up to a 150-fold decrease in (k(cat)/K(m))(DHAP) and up to a 2.7 kcal/mol decrease in the intrinsic phosphodianion binding energy. The data define a linear correlation with slope 1.1, between the intrinsic phosphodianion binding energy and the intrinsic phosphite dianion binding energy for activation of hlGPDH-catalyzed reduction of GA, that demonstrates a role for Q295 in optimizing this dianion binding energy. The R269A mutation of wild-type GPDH results in a 9.1 kcal/mol destabilization of the transition state for reduction of DHAP, but the same R269A mutation of N270A and Q295A mutants result in smaller 5.9 and 4.9 kcal/mol transition-state destabilization. Similarly, the N270A or Q295A mutations of R269A GPDH each result in large falloffs in the efficiency of rescue of the R269A mutant by guanidine cation. We conclude that N270, which interacts for the substrate phosphodianion and Q295, which interacts with the guanidine side chain of R269, function to optimize the apparent transition-state stabilization provided by the cationic side chain of R269.